2023
DOI: 10.1186/s13059-023-02871-7
|View full text |Cite
|
Sign up to set email alerts
|

Not1 and Not4 inversely determine mRNA solubility that sets the dynamics of co-translational events

Abstract: Background The Ccr4-Not complex is mostly known as the major eukaryotic deadenylase. However, several studies have uncovered roles of the complex, in particular of the Not subunits, unrelated to deadenylation and relevant for translation. In particular, the existence of Not condensates that regulate translation elongation dynamics has been reported. Typical studies that evaluate translation efficiency rely on soluble extracts obtained after the disruption of cells and ribosome profiling. Yet ce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 86 publications
(80 reference statements)
0
8
0
Order By: Relevance
“…This suggests that the structure of ribosomes associated with Not4 and Not5 obtained by Beckmann and collaborators is compatible with the last translating ribosomes that accumulate and limit progression of the Xrn1 exonuclease, in the absence of Not4 and Not5, but also after Not1 depletion, since codon‐specific 5′P‐Seq A‐site RDO changes correlate with those in not4Δ and not5Δ (Allen et al, 2021 ; Allen et al, 2023 ). It may seem contradictory that the Not proteins are contributing to co‐translational assembly if they are associated with decay intermediates whose abundance increase in their absence.…”
Section: Translation Elongationmentioning
confidence: 62%
See 2 more Smart Citations
“…This suggests that the structure of ribosomes associated with Not4 and Not5 obtained by Beckmann and collaborators is compatible with the last translating ribosomes that accumulate and limit progression of the Xrn1 exonuclease, in the absence of Not4 and Not5, but also after Not1 depletion, since codon‐specific 5′P‐Seq A‐site RDO changes correlate with those in not4Δ and not5Δ (Allen et al, 2021 ; Allen et al, 2023 ). It may seem contradictory that the Not proteins are contributing to co‐translational assembly if they are associated with decay intermediates whose abundance increase in their absence.…”
Section: Translation Elongationmentioning
confidence: 62%
“…In budding yeast 5 0 P-Seq has been used to analyze translation elongation dynamics of both the soluble and total RNA pools (including the insoluble RNAs) (Allen et al, 2023). From these studies it was noted that changes in A-site RDOs occur according to codon optimality upon depletion of Not proteins in the soluble RNA pool (by Ribo-Seq and 5 0 P-Seq) and that this is mediated by a specific group of mRNAs whose solubility (distribution between soluble and total RNA pools) changes.…”
Section: Mrna Solubility and Translation Elongation Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering heteromers, mRNA co-localization is a prerequisite for co-translational assembly. Such co-localization could be achieved actively through zipcode sequences 63 or through partitioning into specific condensates 64 . Alternatively, random diffusion could suffice to promote nascent chain recognition 65 .…”
Section: Discussionmentioning
confidence: 99%
“…What we know so far about NCAs is limited to their discovery in the context of co-translational assembly of Rpt1 and Rpt2 (Panasenko et al 2019). A recent study using ribosome profiling revealed the pivotal role of Not1 in regulating ribosome pausing on numerous mRNAs, indicating that the NCA regulation might be widespread (Gillen et al 2021;Allen et al 2023). However, maybe not all mRNAs translated in assemblysomes show detectable ribosome pausing by ribosome profiling, because assemblysomes are RNase-resistant (Panasenko et al 2019).…”
Section: Introductionmentioning
confidence: 99%